Acute liver injury due to atomoxetine – A potential lethal outcome of a ubiquitous drug - Singh, Rajesh Kumar; Mallick, Abhishek; Yogesh, Dakhane (Indian Journal of Child Health, 2020)
Atomoxetine is a selective norepinephrine reuptake inhibitor used for the treatment of attention-deficit hyperactivity disorder (ADHD). It’s ubiquitous these days and considered a very safe drug in pediatric practice. However, drug-induced liver injury is a rare but potentially lethal side effect of the drug. We report a 7-year-old boy, a case of ADHD on atomoxetine, who presented with acute liver injury. The boy was initially unresponsive to the treatment but his condition drastically improved after withdrawal of atomoxetine. A derangement of liver function due to atomoxetine often responds only to complete stoppage of the drug.